Developing an interactive graphical user interface for the flexible acceptance sampling plan - Darmawan, Armin; Bohari, Abdul Rahman (Journal of Research and Technology, 2024)
Acceptance sampling plan is one popular approach since decades ago to determine the quality of the lot. Many researchers have developed the acceptance sampling plan in various perspectives and contexts. Generally, two performance measurements are used to evaluate the performance of the acceptance sampling plan including the operational characteristics (OC) and average sample number (ASN). The developed acceptance sampling plan can be used by practitioners to select the appropriate acceptance sampling plan to sentence the quality of the lot. The practitioner can access the tables provided to see the sample requirement and the critical value as the threshold to sentence the lot's quality, then conduct measurements and calculate the sample critical value manually. Further, the practitioner can compare the measured critical value and the threshold critical value. This process is time-consuming, needs several stages, and tends to open human errors in calculating. In this study, the interactive system is developed to reduce the time-consuming, eliminate the stages, and prevent human error. The interactive system is friendly-used, easy to calculate, and provides quick decision-making.